Probation officers’ discretionary decisions in responding to probation violations: The case of Lithuania - Nikartas, Simonas (Probation journal, 2021)
This paper investigates Lithuanian probation officers’ discretionary decisions on probation violations under strict legal regulation. Based on a quantitative survey, this paper analyses hypothetical discretionary decisions according to the type of violation committed by the probationer. The relationship between discretionary decisions and variables such as the probationer’s risk level and sociodemographic characteristics are also analysed. The study revealed that, despite strict legal regulations, which generally require severe action for probation violations, probation officers tend to make more lenient decisions. The study also found that violation type, offender risk level, and probation officer’s age are potential predictors of discretionary decisions.